High directivity microstrip antenna with stopband and passband frequency selective surfaces for 6G at low-THz - Uri Nissanov; Ghanshyam Singh (Institute of Advanced Engineering and Science, 2022)
There is still no high-directivity microstrip antenna with directivity beyond 25 dBi, bandwidth (BW) of more than 24%, which can be used for 6G cellular communication at low-THz at a resonance frequency of 144 GHz. So, duo broadband microstrip antennas have been designed at a resonance frequency of 144 GHz with the Taconic TLY-5 laminate in this work. These designs were carried out with the computer simulation technology microwave studio (CST MWS) software. The first antenna simulation results were compared within an Ansys high-frequency structure simulator (HFSS) software, and the obtained simulation results from both software were in fair consent, supporting the proposed designs. The peak directivity, peak gain, total peak efficiency, and BW obtained for the proposed THz microstrip antennas were 27.01 dBi, 25.3 dB, 78.96%, and 34.21 GHz (24.93%), respectively. Therefore, these antennas can be a base for 6G at low-THz.